Evaluation of the biofilm life cycle between Candida albicans and Candida tropicalis - Atiencia-Carrera, María Belén; Cabezas-Mera, Fausto Sebastián; Vizuete, Karla; Debut, Alexis; Tejera, Eduardo; Machado, António (Frontiers in Cellular and Infection Microbiology, 2022)
Candida tropicalis is an emergent pathogen with a high rate of mortality associated with its biofilm formation. Biofilm formation has important repercussions on the public health system. However, little is still known about its biofilm cycle life. The present study analyzed the biofilm cycle life of Candida albicans and Candida tropicalis during the time (24, 48, 72, and 96h) through biomass assays, colony-forming unit (CFU) counting, and epifluorescence and scanning electron microscopies. Our results showed a significant difference between C. albicans and C. tropicalis biofilms in each biomass and viability assays (Friedman test p <0.05). All-time samples in the biomass and viability assays confirmed statistical differences between Candida species through pairwise Wilcoxon tests (p <0.05). C. albicans demonstrated a lower biomass growth but reached nearly the same level of C. tropicalis biomass at 96h; while, CFU counting assays exhibited a superior number of viable cells within the C. tropicalis biofilm. Statistical differences were also found between C. albicans and C. tropicalis biofilms from 48 and 72h microscopies, demonstrating C. tropicalis with a higher number of total cells within biofilms and C. albicans’ cells with a superior cell area and higher matrix production. Therefore, the present study proved the higher biofilm production of C. tropicalis.